Taste Preference and Metabolic Rate of Trehalose in Chickens - Fuminori Kawabata; Misako Sakai; Hiroki Murasawa; Yu Komine; Kazuhisa Mukai; Yuko Kawabata (The Journal of Poultry Science)
Trehalose (Tre) is composed of two molecules of D-glucose joined by an α,α-1,1 glucosidic linkage. Because Tre is utilized by the gut microbiome and enhances gut immunity in chickens, it is used as a feed ingredient. However, taste preference and metabolic dynamics of Tre in chickens are not fully understood. Therefore, in this study, we investigated the taste preference in chickens for Tre and the metabolism of this disaccharide. In a short-term drinking test, chickens preferred low concentrations of Tre solution while avoiding high concentrations. Instead, in a conditioned taste aversion test, chickens did not show taste aversion to Tre, implying that chickens do not have a sufficient taste for Tre. The initial feed intake rate increased when 0.5% Tre was added. Respiratory gas analysis revealed that intragastric administration of 1.0 M Tre weakly increased the respiratory quotient. Furthermore, approximately 50% of Tre was metabolized in chickens. These results suggest that chickens slightly taste the sweetness of Tre. Moreover, adding Tre to feed increases the chickens’ initial appetite, and they use approximately 50% of Tre as an energy source. This information is relevant for using Tre alone or as a supplement in poultry feed.